Breathing Characteristics and Symptoms of Psychological Distress: An Exploratory Study. Issue 1 (April 2016) - Crockett, Jamie E.; Cashwell, Craig S.; Tangen, Jodi L.; Hall, K. Hridaya; Young, J. Scott
Abstract : In this exploratory study of the relationship between characteristics of breathing and 3 common psychological issues (i.e., symptoms of anxiety, alexithymia, and depression), 79 college‐age adults were examined using self‐report, rater observation, and physiological measures. Results indicated significant positive relationships between dysfunctional breath characteristics and symptoms of both anxiety and alexithymia. A significant positive correlation was found between self‐reported symptoms of dysfunctional breathing and symptoms of depression, but no significant relationships existed between symptoms of depression and either rater‐observed breath characteristics or physiological measures.